Manajemen Pembelajaran Sekolah Dasar di Daerah Tertinggal (Studi Kasus SDN 8 Batu Malang Kecamatan Pulau Maya Kabupaten Kayong Utara) - Fazarudin, Fazarudin; Syofan Syofian; Hendra Wahyudin; Wira Miharja (Universitas Muhammadiyah Surakarta, 2024)
The research aimed at describing; (1) the preparation of earning programs, (2) implementation of earning programs, (3) evaluation of earning programs, (4) earning support factors, (5) earning inhibiting factors, and (6) efforts / solutions regarding earning inhibiting factors. This study uses a qualitative approach to the type of descriptive case study research. The results of this study are: (1) the preparation of earning programs using a dua curriculum namely K13 and KTSP, (2) the implementation of earning programs administratively using two curricula namely K13 and KTSP. However, due to the good condition of the school condition of the condition of the facilities and infrastructure and also the condition of the students so that the earning process is closer to using KTSP, (3) evaluation of the earning program conducted by the teacher there are two types of earning evaluation namely summative evaluation which is meant summative evaluation namely evaluation conducted by the teacher in order to determine the results and development or progress of student earning, and also in addition to summative evaluation the teacher also uses formative evaluation which is an evaluation conducted by the teacher in order to improve and enhance the earning and teaching process, (4) there are two factors supporting earning the first source is the school’s internal environment and also the school’s externa environment, (5) there are two factors that inhibit earning, the first is from the school’s internal environment and also the school’s externa environment, (6) efforts/solutions regarding earning inhibiting factors, there are two ways that schools do in dealing with earning barriers, namely depending on the source of the obstacle. Efforts or solutions made by schools in dealing with the ack of facilities and infrastructure is to ask for more hep from the government or the Office of Education